Analisis CRM Pada Pengelolaan Data Pelanggan Bank BSI Setelah Bercerai Dengan Muhammadiyah - Dzikri, Yushalluna; Hermawansyah, Muhammad Zaky; Pangestu, Muhamad Gibran Akbar; Ariawansyah, Furqon (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2024)
The purpose of this study is to investigate the implementation of Customer Relationship Management (CRM) at Bank Syariah Indonesia (BSI) after the separation with Muhammadiyah. This research uses a descriptive qualitative approach by collecting data through in-depth interviews with BSI management as well as document analysis related to the CRM strategies implemented. The novelty of this research lies in the in-depth understanding of how the implementation of CRM at BSI can affect relationships with customers and success in maintaining their loyalty. The results of the analysis show that the implementation of CRM has had a positive impact in increasing customer satisfaction and loyalty, but the challenges of post-separation organizational culture from Muhammadiyah were also identified as important factors that need to be considered.